2015
DOI: 10.1002/jor.22891
|View full text |Cite
|
Sign up to set email alerts
|

Restricted differentiation potential of progenitor cell populations obtained from the equine superficial digital flexor tendon (SDFT)

Abstract: The aim of this study was to characterize stem and progenitor cell populations from the equine superficial digital flexor tendon, an energy‐storing tendon with similarities to the human Achilles tendon, which is frequently injured. Using published methods for the isolation of tendon‐derived stem/progenitor cells by low‐density plating we found that isolated cells possessed clonogenicity but were unable to fully differentiate towards mesenchymal lineages using trilineage differentiation assays. In particular, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 27 publications
(56 reference statements)
6
34
1
Order By: Relevance
“…TPCs were isolated from superficial digital flexor tendons of three healthy (4-6 years of age) adult horses using protocols previously described [14][15][16]24]. These cells were characterized via cell surface marker expression (CD 44 + , CD29 + , CD90 + , and CD45 -) and in vitro trilineage differentiation as previously described [15,16,24]. An intact forelimb superficial flexor tendon was harvested from young adult horses euthanized for reasons unrelated to musculoskeletal disease.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…TPCs were isolated from superficial digital flexor tendons of three healthy (4-6 years of age) adult horses using protocols previously described [14][15][16]24]. These cells were characterized via cell surface marker expression (CD 44 + , CD29 + , CD90 + , and CD45 -) and in vitro trilineage differentiation as previously described [15,16,24]. An intact forelimb superficial flexor tendon was harvested from young adult horses euthanized for reasons unrelated to musculoskeletal disease.…”
Section: Methodsmentioning
confidence: 99%
“…Complete DMEM was then substituted with osteogenic medium (complete DMEM supplemented with 10 mM β-glyceraldehyde-3-phosphate, 50 μg/mL ascorbic acid, 100 nM dexamethasone) or osteogenic medium with 0.07 or 0.7 nM insulin (Humulin® U-100, Lilly, USA). The medium was replaced every 48-72 hours [15,16]. The cultures were maintained for 14 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang and Wang reported that rabbit patellar TPCs had larger colonies and proliferated more rapidly than Achilles TPCs in monolayer culture 88 . Williamson et al reported that equine superficial digital flexor tendon TPCs had restricted differentiation capabilities in monolayer culture in that they were unable to undergo adipogenesis 89 .…”
Section: Gene Expressionmentioning
confidence: 99%